Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1088/1741-2552/abd2c9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel transcranial temporally interfering stimulation (tTIS): application to living mice brain

Abstract: Objective. Transcranial temporally interfering stimulation (tTIS) is a noninvasive neuromodulation method, which has been reported to be able to affect the activity of small neuronal populations. To pinpoint smaller regions of the brain, a multi-channel tTIS strategy is proposed with larger numbers of electrodes and multiple sets of interfering fields. Approach. First, a computational model is adopted to prove the concept of multi-channel tTIS theoretically. Besides, animal experiments are implemented to activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Multiscale modeling was applied to replicate the experiments conducted in Grossman et al (2017), the primary findings of which were: (i) beat frequency does not influence the threshold for the range considered, (ii) the threshold increases with an increase in the carrier frequency, and (iii) the stimulation region changes according to the ratio between the two injection currents. These were also reproduced in another study (Song et al, 2020). Our multiscale modeling replicated the three experiments for the first time using realistically shaped generated current effects on the neuronal model.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Multiscale modeling was applied to replicate the experiments conducted in Grossman et al (2017), the primary findings of which were: (i) beat frequency does not influence the threshold for the range considered, (ii) the threshold increases with an increase in the carrier frequency, and (iii) the stimulation region changes according to the ratio between the two injection currents. These were also reproduced in another study (Song et al, 2020). Our multiscale modeling replicated the three experiments for the first time using realistically shaped generated current effects on the neuronal model.…”
Section: Discussionsupporting
confidence: 66%
“…Instead, a small difference in the frequencies of the two injection currents may generate a beat wave (modulation envelope) causing neural stimulation. Previous studies have shown promising results for motor area stimulation in mice ( Grossman et al, 2017 ; Song et al, 2020 ). In addition, various efforts have been made to clarify the mechanism regarding biophysics using neural models ( Karimi et al, 2019 ; Cao and Grover, 2020 ; Howell and McIntyre, 2020 ; Mirzakhalili et al, 2020 ; Esmaeilpour et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A multi-channel tTIS study on mice [31] indicated that targeting accuracy significantly improves when considering a six-channel (six electrode pairs) tTIS, performing 70.2% better than the single-channel (one electrode pair) tTIS. Furthermore, in [31], stimulation targeting appeared to be less affected when selecting different electrode pairs. In summary, Song et al [31] showed that more channels make the tTIS method more independent of the exact electrode placement while increasing the focality.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that we used two electrode pairs in this study, the focality resolution was limited. This problem can be addressed by using more electrode pairs for stimulation [31].…”
Section: Qrswlpl]hgmentioning
confidence: 99%
“…The characteristics of an envelope may predict the regions of TI stimulation (Gomez-Tames et al, 2021 ). Multichannel array electrodes for TI stimulation enhance focality and reduce scalp sensation in computational modeling and mouse experiments (Song et al, 2020 ). Wang H. et al ( 2020 ) fabricated a TI stimulator that measures bioimpedance in real time and proposed an approach that can easily locate the target position.…”
Section: Temporal Interference Stimulationmentioning
confidence: 99%